Multiphase Flow Simulations to Explore Novel Technique of Air Injection to Mitigate Silt Erosion in Hydro Turbines - P. Dhiman; A. Bhat; A. Karn (Journal of Applied Fluid Mechanics)
Hydropower is increasingly recognized as a sustainable energy source due to its minimal environmental impact, a crucial factor in meeting global energy demands. However, the efficiency of hydropower plants (particularly in the Himalayan region) can be hampered by wear and tear of essential components like hydroturbine blades, runners, guide vanes, and nozzles, caused by silt particles in water streams. This study proposes an innovative solution to mitigate silt erosion by implementing a partial air shield on the pressure surface of hydrofoils. Through numerical simulations, the study investigates the interaction between quartz particle-water suspension and injected air on a NACA 4412 hydrofoil. The Euler-Euler-Lagrange model combined with the K-omega SST turbulence scheme is observed to accurately predict erosion wear behavior with and without air injection. The investigation reveals two significant phases. Initially, a comparison between scenarios with and without air injection shows a noticeable reduction in erosion rate when air is introduced over the surface. To further illustrate this reduction, the study increases the silt suspension levels from 2500 ppm to 5000 ppm and the air injection speed from 7.5 m/s to 17.5 m/s, while maintaining a constant hydrofoil angle of attack at 10° and an air-injection angle of 30°. In the subsequent phase, detailed exploration of various air injection parameters reveals an inverse relationship between air injection speed and erosion rate. This study provides comprehensive data sheets illustrating results for different parameter ranges, suggesting that air entrainment on hydroturbine runners can effectively reduce wear due to silt.